Evaluation of the "safe multidisciplinary app-assisted remote patient-self-testing (SMART) model" for warfarin home management during the COVID-19 pandemic: study protocol of a multi-center randomized controlled trial - Lei Chen; Yang-Zhao Zhou; Xin-Min Zhou; Li-Ming Liu; Ping Xu; Xia Zhang; Sheng-Lan Tan (BMC, 2021)
Abstract Background Warfarin treatment requires frequent monitoring of INR (international normalized ratio) to adjust dosage in a therapeutic range. In China, patients living in small towns usually go to tertiary hospitals to get warfarin monitoring and dosing, resulting in low frequencies of follow-ups and high incidence of complications. Influenced by the COVID-19 pandemic, patients on warfarin have further reduced their visits to healthcare institutions. While patient self-testing (PST) via using a point-of-care testing device for INR measuring at home has been widely used in developed countries and demonstrated improved clinical outcomes compared to usual care in clinics, it is rarely applied in developing countries, including China. This proposed study will develop and assess the "Safe Multidisciplinary App-assisted Remote patient-self-Testing (SMART) model" for warfarin home management in China during the COVID-19 pandemic. Methods This is a multi-center randomized controlled trial. We will carry out the study in three county hospitals, three small tertiary hospitals and three large tertiary hospitals with anticoagulation clinics in Hunan province of China. Eligible patients will be randomly assigned to the SMART model group (n = 360) or the control group (usual care clinic group, n = 360; anticoagulation clinic group, n = 120). Patients in the SMART model group do PST at home once every two to 4 weeks. Controls receive usual care in the clinics. All the patients will be followed up through outpatient clinics, phone call or online interviews at the 3rd, 6th, 9th and 12th month. The percentage of time in therapeutic range (TTR), incidence of warfarin associated major bleeding and thromboembolic events and costs will be compared between the SMART model group and control groups. Discussion Patients in the SMART model group would show improved TTR, lower incidence of complications and better quality of life compared to the control groups. Our design, implementation and usage of the SMART model will provide experience and evidence in developing a novel model for chronic disease management to solve the problem of healthcare service maldistribution, an issue particularly obvious in developing countries during the COVID-19 pandemic. Trial registration ChiCTR, ChiCTR 2000038984 . Registered 11 October, 2020.